Radiostereometric Analysis Study of Tantalum Compared with Titanium Acetabular Cups and Highly Cross-Linked Compared with Conventional Liners in Young Patients Undergoing Total Hip Replacement - Ayers, David C. (J Bone Joint Surg Am, 2015)
BACKGROUND: Radiostereometric analysis provides highly precise measurements of component micromotion relative to the bone that is otherwise undetectable by routine radiographs. This study compared, at a minimum of five years following surgery, the micromotion of tantalum and titanium acetabular cups and femoral head penetration in highly cross-linked polyethylene liners and conventional (ultra-high molecular weight polyethylene) liners in active patients who had undergone total hip replacement. METHODS: This institutional review board-approved prospective, randomized, blinded study involved forty-six patients. Patients were randomized into one of four cohorts according to both acetabular cup and polyethylene liner. Patients received either a cementless cup with a titanium mesh surface or a tantalum trabecular surface and either a highly cross-linked polyethylene liner or an ultra-high molecular weight polyethylene liner. Radiostereometric analysis examinations and Short Form-36 Physical Component Summary, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), University of California Los Angeles (UCLA) activity, and Harris hip scores were obtained preoperatively, postoperatively, at six months, and annually thereafter. RESULTS: All patients had significant improvement (p < 0.05) in Short Form-36 Physical Component Summary, WOMAC, UCLA activity, and Harris hip scores postoperatively. On radiostereometric analysis examination, highly cross-linked polyethylene liners showed significantly less median femoral head penetration at five years (p < 0.05). Steady-state wear rates from one year to five years were 0.04 mm per year for ultra-high molecular weight polyethylene liners and 0.004 mm per year for highly cross-linked polyethylene liners. At the five-year follow-up, the median migration (and standard error) was 0.05 ± 0.20 mm proximally for titanium cups and 0.21 ± 0.05 mm for tantalum cups. CONCLUSIONS: In this young population who had undergone total hip replacement, radiostereometric analysis showed significantly less femoral head penetration in the highly cross-linked polyethylene liners compared with that in the conventional ultra-high molecular weight polyethylene liners. Penetration rates were one order of magnitude less in highly cross-linked polyethylene liners compared with ultra-high molecular weight polyethylene liners. There was no significant difference in proximal migration between the tantalum and titanium acetabular cups through the five-year follow-up (p > 0.19). LEVEL OF EVIDENCE: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.